2002
DOI: 10.1086/344409
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Strengths in the Hot Spots and Lobes of Three Powerful Fanaroff‐Riley Type II Radio Sources

Abstract: We have made deep Chandra observations of three powerful FRII radio sources: two quasars (3C 263 and 3C 351) and one radio galaxy (3C 330). X-ray emission from hotspots and lobes, as well as from the active nucleus, is detected in each source.We model the hotspots' synchrotron spectra using VLA, BIMA and Hubble Space Telescope data. In 3C 263 and 3C 330, the hotspots' X-ray emission is at a level consistent with being synchrotron self-Compton (SSC) emission, with a hotspot magnetic field close to the equiparti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
213
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(243 citation statements)
references
References 67 publications
30
213
0
Order By: Relevance
“…Hardcastle et al 2002;Croston et al 2004Croston et al , 2005Ineson et al 2017). In this technique the X-ray emission upscattered from the synchrotronemitting electrons is compared to that expected if their energy densities are in equipartition with the magnetic field.…”
Section: Radio Lobe Plasma Compositionmentioning
confidence: 99%
“…Hardcastle et al 2002;Croston et al 2004Croston et al , 2005Ineson et al 2017). In this technique the X-ray emission upscattered from the synchrotronemitting electrons is compared to that expected if their energy densities are in equipartition with the magnetic field.…”
Section: Radio Lobe Plasma Compositionmentioning
confidence: 99%
“…The simple one-zone model with a near equipartition magnetic field strength provides a good description of the available data. Hardcastle et al (2002) used more complicated spectral and spatial models for three sources, and found that this did not have a significant effect on the derived plasma parameters. We are therefore confident in our parameter estimates using this "first-order" one-zone model.…”
Section: Synchrotron Self-compton Modelingmentioning
confidence: 99%
“…Brunetti et al (1999) and reported the detection of X-ray emission in the lobes of 3C 219 and in 3C 215 and 3C 334, respectively, that possibly arises from inverse Compton scattering of IR photons from the quasar nucleus. IC/3K lobe emission has been reported in several radio galaxies, including Fornax A (Kaneda et al 1995;Feigelson et al 1995), Centaurus B (Tashiro et al 1998), A0038À096 (Bagchi, Pislar, & Neto 1998), 3C 295 (Brunetti et al 2001), 3C 330 (Hardcastle et al 2002), and 3C 263 (Crawford & Fabian 2003). Synchrotron self-Compton (SSC) emission was reported in the hot spots of several powerful galaxies, including Cygnus A (Harris, Carilli, & Perley 1994), 3C 295 (Harris et al 2000), 3C 273 (Röser et al 2000), 3C 123 (Hardcastle, Birkinshaw, & Worrall 2001), 3C 207 , and 3C 263 and 3C 330 (Hardcastle et al 2002).…”
Section: Introductionmentioning
confidence: 98%